2021
DOI: 10.1080/14459795.2021.2002384
|View full text |Cite
|
Sign up to set email alerts
|

How gambling harms the wellbeing of family and others: a review

Abstract: Problem gambling can have negative impacts on both harmed gamblers, and those people close to them (concerned significant others; CSOs). Experiencing these gambling-related harms can have a significant impact on a person's wellbeing and quality of life. Recently, the focus of research on people with gambling problems has expanded from exploring gambling-related harms and specific psychological outcomes, to include global evaluations of health and wellbeing. However, it is also important to understand the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…termed as 'affected others' (AOs). Research has tried to estimate the prevalence of AOs in the general population and has shown that problem gambling impacts a greater proportion of the population than the gambling individual alone (Tulloch et al, 2021). In the UK, Gunstone et al (2021) found that 6.5% of the UK population were individuals who 'knew someone with a gambling problem (either currently, or in the past) and feel that they have personally experienced negative effects from this person's gambling behaviour'.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…termed as 'affected others' (AOs). Research has tried to estimate the prevalence of AOs in the general population and has shown that problem gambling impacts a greater proportion of the population than the gambling individual alone (Tulloch et al, 2021). In the UK, Gunstone et al (2021) found that 6.5% of the UK population were individuals who 'knew someone with a gambling problem (either currently, or in the past) and feel that they have personally experienced negative effects from this person's gambling behaviour'.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that there is a large degree of cross-over in the experiences of gambling-related harms by the gambling individual and by AOs (Li et al, 2017). Harms to AOs impact in numerous ways, including financial problems, reduced emotional and psychological wellbeing, harm to physical health, and significant breakdowns in the relationship with the individual who gambles, characterised by a lack of trust and interpersonal conflicts, which can include violence (Banks et al, 2018;Castren et al, 2021;Dowling et al, 2021;Gunstone et al, 2021;Holdsworth et al, 2013;Langham et al, 2015;Lind et al, 2022;Riley et al, 2018;Subramaniam et al, 2017;Tulloch et al, 2021;Velleman et al, 2015). Research has also illustrated that AOs were more likely to engage in health risk behaviours including harmful alcohol use, daily tobacco smoking, over-eating, as well as risky gambling behaviours themselves (Dowling et al, 2021;Lind et al, 2022;Riley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gambling-related harms span across numerous domains, from financial impacts and emotional distress to lesser considered factors such as reduced work performance and cultural harms [2]. Harms do not only impact the individual gambler, with a recent literature review highlighting the significant negative effects gambling can have on concerned significant others [3]. Given the wide-ranging impact of gambling-related harm at both an individual and population level, much focus within the literature has been dedicated to assessing factors that contribute towards such harm.…”
Section: Introductionmentioning
confidence: 99%
“…Risk gambling encompasses behaviours such as betting for increasing amounts of money or borrowing money to keep gambling ( CAN, 2021 ). Early onset of problem gambling is associated with an elevated risk of developing gambling problems later in life but may also have short- and long-term social, educational, economic and health-related consequences, both for the individual and for people in their immediate social environment ( Riley et al, 2021 , Tulloch et al, 2022 ). Counteracting adolescent gambling is thus a public health issue and identifying conditions that protect youth at risk of gambling is of great importance.…”
Section: Introductionmentioning
confidence: 99%